Automated coating procedures to produce poly(ethylene glycol) brushes in fused‐silica capillaries. Issue 3 (29th December 2016) - Poulsen, Nicklas N.; Østergaard, Jesper; Petersen, Nickolaj J.; Daasbjerg, Kim; Iruthayaraj, Joseph; Dedinaite, Andra; Makuska, Ricardas; Jensen, Henrik
Abstract : Many bioanalytical methods rely on electrophoretic separation of structurally labile and surface active biomolecules such as proteins and peptides. Often poor separation efficiency is due to surface adsorption processes leading to protein denaturation and surface fouling in the separation channel. Flexible and reliable approaches for preventing unwanted protein adsorption in separation science are thus in high demand. We therefore present new coating approaches based on an automated in‐capillary surface‐initiated atom transfer radical polymerization process (covalent coating) as well as by electrostatically adsorbing a presynthesized polymer leading to functionalized molecular brushes. The electroosmotic flow was measured following each step of the covalent coating procedure providing a detailed characterization and quality control. Both approaches resulted in good fouling resistance against the four model proteins cytochrome c, myoglobin, ovalbumin, and human serum albumin in the pH range 3.4−8.4. Further, even samples containing 10% v/v plasma derived from human blood did not show signs of adsorbing to the coated capillaries. The covalent as well as the electrostatically adsorbed coating were both found to be stable and provided almost complete suppression of the electroosmotic flow in the pH range 3.4−8.4. The coating procedures may easily be integrated in fully automated capillary electrophoresis methodologies.